Errors In English Ads And Fallacious Trends Of Job Advertisements In Jakarta - Masda Surti Simatupang; Yusniaty Galingling (Lingua Cultura, 2012)
Article investigated the errors found in job advertisements from Kompas newspapers and the fallacious trends. The methodology used in this paper was descriptive qualitative. Data were gathered randomly from job advertisements from Kompas in 2008. The data were analyzed through the following steps: first, the data were gathered and classified into errors from L1 interference, and errors from lack of grammatical knowledge. After causes of errors were explained, then the fallacious trends were described. Data showed the inconsistency of translating Job’s titles because of L1 interference. Errors due to lack of grammatical knowledge were classified into four categories of omission, addition, and substitution. From 44 data of omission and addition, the inflection (ending –s and -ed) mostly occured. There were 24 cases found from the errors of substitution regarding the class words, preposition, and agreement. Fallacious trends that Job’s ads written in English that were free from errors proved to be contrary to the fact.